Implementation of Green Practices in Improving Service Quality of Food & Beverage Department at Hotel Indigo Bali Seminyak Beach - Ni Putu Trisna Puspita Dewi; I Gusti Agung Bagus Mataram; Made Sudiarta; I Putu Budiarta (Yayasan Sinergi Widya Nusantara, 2023)
Purpose: This study aims to determine the implementation of green practices in improving the quality of service in the food & beverage department at Hotel Indigo Bali Seminyak Beach. Research methods: The data collection methods used in this study were observations, questionnaires, interviews and literature studies. The analysis technique used is descriptive qualitative, namely explaining systematically the data obtained during the study, so as to describe the state or status of a problem clearly and descriptively quantitatively using a 4-level likert scale. The number of respondents used was 12 respondents from the food & beverage department staff. Findings: Overall the application of green practices in service quality has been applied optimally. There are several stages in the process of improving service quality which in the application of green action the average value is 3.11 which means that it has been maximally applied, green food average value is 3.06 which means it is quite optimally applied, green dionation with an average value of 2.86 which is quite optimally applied. Implication: There is a need to evaluations, conducting SOP training and conducting supervision while working.